Guided Filter for Grayscale, RGB and HSV color space (International Journal of Engineering and Computer Science, 2016)
Guided filter is derived from a local linear model and in guided filter filtering output is computed by referring guidance image, which can be input image itself or different image. The Guided filter can be used as edge preserving smoothing and gradient preserving operator, it shows better result near edges. My work is focused on implementing guided filter algorithm, which is 2D algorithm. This algorithm is applicable to gray-scale image and color images like RGB and HSV by separating each color channel. The experiments show that the guided filter is effective in computer vision and graphics applications as well as edge preserving smoothing, detail enhancement, denoising, etc.